Mengintegrasikan AI dalam penulisan buku ajar: Pelatihan inovatif bagi guru - Hartini Haritani; Hary Murcahyanto; Sitti Rohmi Djalilah (Universitas Hamzanwadi, 2025)
Digital education requires teachers to develop systematic textbooks while using technology responsibly. This paper reports a community service program on integrating artificial intelligence (AI) into textbook writing for teachers at SMAN 1 Selong and MA Mu’alimat NWDI Pancor, conducted from August to September 2025. The program consisted of four stages: socialization, technical workshop, mentoring, and presentation–evaluation. Participants practiced using ChatGPT, Grammarly, Turnitin, Canva, and reference-management tools to support drafting and editing. The results show that 40 textbook drafts (at least three chapters each) were produced and can be further refined for classroom use. In addition, 70% of participants were able to independently operate at least three AI-based tools. These findings suggest that hands-on training combined with mentoring can strengthen teachers’ technical capacity and accelerate the textbook-writing process, supporting more relevant and innovative teaching materials in schools